2021
DOI: 10.1016/j.pmedr.2021.101361
|View full text |Cite
|
Sign up to set email alerts
|

Police brutality, medical mistrust and unmet need for medical care

Abstract: Highlights Police brutality can shape health by limiting access to health care. Police brutality is associated with greater odds of unmet need for medical care. This association is partly explained by medical mistrust.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…These findings hold several implications for public health practice. Existing evidence suggests that incarcerated populations have greater degrees of distrust of the medical system (Alang et al, 2020(Alang et al, , 2021Brayne, 2014;Howerton et al, 2007;Porter, 2019;Vandergrift & Christopher, 2021). Thus, it may be that those who have been incarcerated are less trusting of medical guidance surrounding steps to mitigate COVID-19, as well as the safety and efficacy of vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings hold several implications for public health practice. Existing evidence suggests that incarcerated populations have greater degrees of distrust of the medical system (Alang et al, 2020(Alang et al, , 2021Brayne, 2014;Howerton et al, 2007;Porter, 2019;Vandergrift & Christopher, 2021). Thus, it may be that those who have been incarcerated are less trusting of medical guidance surrounding steps to mitigate COVID-19, as well as the safety and efficacy of vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…Our study results add to this literature by indicating that COVID-19-related financial hardships are associated with medical mistrust. Prior research has found that distrust in one institution, such as experiences with police, breeds distrust in other institutions including healthcare [ 23 , 31 , 59 ]. As such, one possible explanation for our finding is that financial hardships due to COVID-19 may well impact trust in government, employers, or schools to provide equitable educational and economic opportunities, and distrust in these institutions could carry over to increased distrust of healthcare institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Police brutality, as one format of structural racism, has been and continues to be a problem. Several social campaigns, including #SayHisName, #SayHerName, and #SayTheirNames, have attempted to raise awareness of the issue's scope [6,7].…”
Section: Introductionmentioning
confidence: 99%